Penyelenggarakan School Based Inset Sebagai Upaya Peningkatan Profesionalisme Guru dalam Kegiatan Belajar Mengajar di SDNo.75/IX Muaro Kumpeh Tahun Pelajaran 2019 / 2020 - Dameri Situmeang (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research is supported by: 1) For the work of teachers in carrying out teaching and learning activities is very varied and the quality of the teacher varies. 2) The progress and development of science and technology (IPTEK) requires adjustment and professional development of teachers to be able to develop education in schools. 3) Ministerial Decree: Number 84/2002 regarding professional positions and credit figures requires teachers to further improve their professional abilities, work, excel in carrying out their daily school duties. 4) The natural conditions of Indonesia require a communication system and professional development of teachers by using multi dimensional. From the above background, the writer conducted a research entitled "Organizing School Based Inset as an Effort to Increase Teacher Professionalism in Teaching and Learning Activities at SD No.75 / IX Muaro Kumpeh Academic Year2019/2020". The results of the study show that School Based Inset at SDNo.75 / IX Muaro Kumpeh is a very important instrument to advance the teaching system in the classroom and School Based Inset has an important role in efforts to improve teacher professionalism in teaching and learning activities, because it makes teachers more advanced, insightful. more modern science and technology.